2010
DOI: 10.1177/0265407510386191
|View full text |Cite
|
Sign up to set email alerts
|

Cohort differences in having and retaining friends in personal networks in later life

Abstract: Friendship has increased in importance during the last few decades. The study examines whether friendship has become more prevalent in personal networks of older adults. Three cohorts of older persons have been followed since 1992 for 17 years in the Longitudinal Aging Study Amsterdam. The younger cohort had friends more often and retained friends longer than two older cohorts. The differences are related to personal choice, relational competence and greater structural opportunities for making and keeping frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
23

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 36 publications
3
49
0
23
Order By: Relevance
“…In previous studies we observed cohort differences in age-related decline in social outcomes, as volunteering (Broese van Groenou & Van Tilburg, 2012) and having friends in the social network (Stevens & Van Tilburg, 2011). In the present study we controlled for sociostructural factors, which may in part take care of these cohort differences.…”
Section: Discussionmentioning
confidence: 80%
“…In previous studies we observed cohort differences in age-related decline in social outcomes, as volunteering (Broese van Groenou & Van Tilburg, 2012) and having friends in the social network (Stevens & Van Tilburg, 2011). In the present study we controlled for sociostructural factors, which may in part take care of these cohort differences.…”
Section: Discussionmentioning
confidence: 80%
“…In most cases, men maintain less informal social support and women retain stronger personal networks in case of need. The importance of gender in informal support networks is due to the fact that, as Stevens and van Tilburg () have indicated, women maintain friends of the same gender longer than men. Thus, when women reach an advanced age they have more extensive networks of friends of their own gender than do men (Stevens and van Tilburg, ).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults are short of confidant friends [66] but also seem more satisfied with the friends they still have [67]. A friend is someone you can trust, who will not judge you, who supports you, who has the patience to listen, and who does not claim social space.…”
Section: Apparatus/materialsmentioning
confidence: 99%